Crystalline silica activates the T-cell and the B-cell antigen receptor complexes and induces T-cell and B-cell proliferation - Theodoros Eleftheriadis; Georgios Pissas; Sotirios Zarogiannis; Vassilios Liakopoulos; Ioannis Stefanidis (Taylor & Francis Group, 2019)
Silicosis is an occupational fibrotic lung disease, which is associated with an increased incidence of autoimmune diseases. The effect of crystalline silica on the immune system is thought to be mediated by the antigen presenting cells. However, the direct effect of silica on T-cells and B-cells has not been evaluated adequately. For this purpose, CD4(+)T-cells and B-cells from 10 healthy individuals were isolated and cultured with or without Min-U-Sil 5. Cell proliferation was assessed with BrdU assay. In cell proliferation experiments, tacrolimus, an inhibitor of the signal transduction derived from the activation of the T-cell or the B-cell antigen receptor (BCR) complex, was also used. The levels of phosphorylated zeta and phosphorylated Igα, indicative of the T-cell and BCR complex activation respectively, and of the transcription factor c-Myc, required for cell proliferation, were assessed by Western blotting. Crystalline silica triggered CD4(+)T-cell and B-cell proliferation, while tacrolimus significantly decreased the silica-induced proliferation in both cell types. Crystalline silica enhanced the level of phosphorylated zeta and phosphorylated Igα in CD4(+)T-cells and B-cells, respectively. In both cell types, treatment with silica increased c-Myc expression. Thus, crystalline silica may induce T-cell and B-cell proliferation by activating T-cell and BCR complexes. It is likely that the direct activation of CD4(+)T-cells and B-cells by silica crystals detected in this study circumvents many self-tolerance check-points and offers a mechanistic explanation for the crystalline silica-induced autoimmune diseases.